Analyzing the Impacts of Course and Training Institution Management on Education Services for Communities during the Covid-19 Pandemic - Herwina, Wiwin; Miradj, Safri (Journal of Nonformal Education, 2021)
The unexpected and rapid spread of COVID-19 throughout the world has made the course and training institution management face various problems, such as adapting new learning habits by using blended learning, tutors and students who have not well mastered the utilization of online learning media, and tutors’ ability to train the Learners to quickly adapt and utilize the new technology when learning from home. This study aimed to analyze the impacts of course and training institution management on educational services for communities during the COVID-19 pandemic. The analysis was conducted on six education program management indicators starting from planning to development. Furthermore, the impacts of course and training activities performed by the institutions during the COVID-19 pandemic were also analyzed. This study was participated by 27 course and training institutions in Tasikmalaya. A qualitative research method was performed to collect the research data. The research found that the course and training institution management was in accordance with the concept of education program management starting from planning to supervising. In addition, the impacts of course and training institution the management during the COVID-19 pandemic included: (a) developing the managers’ ability to deal with the unexpected situations; (b) developing the tutors’ and students’ ability related to skills mastered after training and online learning media; (c) increasing the existence of institutions; (d) increasing the public trust to the related institutions. Meanwhile, the institutional infrastructure completeness was strengthened by making partnerships with the other institutions and the industrial world, as well as increasing the quantity and quality of graduates. However, the managers did not feel the impacts.